2007
DOI: 10.1007/s10669-007-9029-4
|View full text |Cite
|
Sign up to set email alerts
|

Soil lead contamination at child day care centers in the greater Cincinnati area

Abstract: Lead concentrations were determined for soil samples collected at 37 child day care centers located within the greater Cincinnati area. Soil samples were collected within 1.5 m of the exterior walls and throughout the remainder of the outdoor playgrounds of each of the child day care facilities. The soil lead concentrations were utilized as indicators of lead contamination from vehicle emissions and lead based paints. Mean lead concentrations were determined through Inductively Coupled PlasmaMass Spectrometry.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Other research groups have reported on selected chemical and biological agents such as pesticides and other persistent organic pollutants [8,[10][11][12][13][14], PCBs [15,16], brominated flame retardants [17], perfluorinated compounds [17][18][19], metals [14,17,[20][21][22][23][24][25][26][27][28][29][30], and allergens (including dust mite, cockroach, cat, dog, endotoxins, horse, fungi) in both the indoor and outdoor childcare center environment in limited studies in the United States and globally. Collectively, this body of research shows that children may be exposed to numerous chemical and biological agents while in center-based care, yet we don't understand how exposure to myriad chemical and biological agents may affect children's health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Other research groups have reported on selected chemical and biological agents such as pesticides and other persistent organic pollutants [8,[10][11][12][13][14], PCBs [15,16], brominated flame retardants [17], perfluorinated compounds [17][18][19], metals [14,17,[20][21][22][23][24][25][26][27][28][29][30], and allergens (including dust mite, cockroach, cat, dog, endotoxins, horse, fungi) in both the indoor and outdoor childcare center environment in limited studies in the United States and globally. Collectively, this body of research shows that children may be exposed to numerous chemical and biological agents while in center-based care, yet we don't understand how exposure to myriad chemical and biological agents may affect children's health and well-being.…”
Section: Introductionmentioning
confidence: 99%
“…Volume of traffic pollution depends on the distance from the road, topography and traffic intensity (Niesiobędzka & Krajewska 2007, Button 2008. Dust borne heavy metals accumulate in the topsoil due to the atmospheric deposition by sedimentation, impaction and interception (Li et al 2001, Sezgin et al 2006, Lu et al 2009).…”
Section: Introductionmentioning
confidence: 99%